2021
DOI: 10.1007/s00442-021-04981-0
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of environmental and dispersal filters on phylogenetic and taxonomic beta diversity patterns in Amazonian tree communities

Abstract: Environmental and dispersal filters are key determinants of species distributions of Amazonian tree communities. However, a comprehensive analysis of the role of environmental and dispersal filters is needed to understand the ecological and evolutionary processes that drive phylogenetic and taxonomic turnover of Amazonian tree communities. We compare measures of taxonomic and phylogenetic beta diversity in 41 one-hectare plots to test the relative importance of climate, soils, geology, geomorphology, pure spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 83 publications
(163 reference statements)
2
7
1
Order By: Relevance
“…The analysis of influencing factors has revealed that both environmental and geographical limitations significantly constrained the maintenance of beta diversity in plant communities in the Nujiang dry and hot valley. We observed that the impact of environmental limitations was notably higher, being 4-6 times greater than that of dispersal limitations, with climate and soil factors playing a critical role in environmental limitations (Andino et al, 2021). In contrast to the findings observed in the Dulongjiang and Yuanjiang valleys of Southwest China, the results indicated that geographic distance played a relatively minor role at the local scale in the Nujiang dry and hot valley (Li et al, 2016;Meng et al, 2017).…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…The analysis of influencing factors has revealed that both environmental and geographical limitations significantly constrained the maintenance of beta diversity in plant communities in the Nujiang dry and hot valley. We observed that the impact of environmental limitations was notably higher, being 4-6 times greater than that of dispersal limitations, with climate and soil factors playing a critical role in environmental limitations (Andino et al, 2021). In contrast to the findings observed in the Dulongjiang and Yuanjiang valleys of Southwest China, the results indicated that geographic distance played a relatively minor role at the local scale in the Nujiang dry and hot valley (Li et al, 2016;Meng et al, 2017).…”
Section: Discussioncontrasting
confidence: 90%
“…Such differences in the beta composition patterns of different life forms may contribute to variations in plant community composition. The analysis has shown that climate factors are stronger predictive factors at wider spatial scales (50 km 2 ), whereas soil and topographic factors become relatively more important at medium (5 km 2 ) and finer (0.5 km 2 ) scales (Andino et al, 2021). Soil factors, in particular, were identified as important limiting factors in this study.…”
Section: Discussionmentioning
confidence: 58%
“…Phylogenetic diversity peaks at intermediate precipitation in lowland South American forests and savannas (Neves et al 2020), with semideciduous forests containing specialised lineages from both extremes, whilst the phylogenetic beta‐diversity of Colombian plant assemblages increases with temperature but remains unaffected by differences in precipitation (González‐Caro et al 2014). Climate is a strong predictor of both taxonomic and phylogenetic turnover of tree species in Amazonia, but overall phylogenetic turnover is low (Andino et al 2021). Patterns of phylogenetic alpha‐ and beta‐diversity over environmental gradients remain largely unstudied in savannas.…”
Section: Introductionmentioning
confidence: 99%
“…The role of soil variation in determining floristic composition has been also broadly recognized, particularly at intermediate and landscape scales (Phillips et al, 2003a;Tuomisto et al, 2003b;Guevara Andino et al, 2021). In the hitherto most exhaustive review of the effects of soil factors on floristic composition in tropical forests, Sollins (1998) indicated that the most important edaphic variables that affect evergreen lowlands forests were, in a decreasing order of importance: phosphorus availability, aluminum content, moisture (in terms of drainage and water-holding capacity) and availability of base-metal cations (potassium, calcium, and magnesium).…”
Section: Introductionmentioning
confidence: 99%